Targeting Cullin-RING E3 Ligases for Radiosensitization: From NEDDylation Inhibition to PROTACs - Zheng, Shuhua; Tao, Wensi (Frontiers in Oncology, 2020)
As a dynamic regulator for short-lived protein degradation and turnover, the ubiquitin-proteasome system (UPS) plays important roles in various biological processes, including response to cellular stress, regulation of cell cycle progression, and carcinogenesis. Over the past decade, research on targeting the cullin-RING (really interesting new gene) E3 ligases (CRLs) in the UPS has gained great momentum with the entry of late-phase clinical trials of its novel inhibitors MLN4924 (pevonedistat) and TAS4464. Several preclinical studies have demonstrated the efficacy of MLN4924 as a radiosensitizer, mainly due to its unique cytotoxic properties, including induction of DNA damage response, cell cycle checkpoints dysregulation, and inhibition of NF-κB and mTOR pathways. Recently, the PROteolysis TArgeting Chimeras (PROTACs) technology was developed to recruit the target proteins for CRL-mediated polyubiquitination, overcoming the resistance that develops inevitably with traditional targeted therapies. First-in-class cell-permeable PROTACs against critical radioresistance conferring proteins, including the epidermal growth factor receptor (EGFR), androgen receptor (AR) and estrogen (ER) receptor, cyclin-dependent kinases (CDKs), MAP kinase kinase 1 (MEK1) and MEK2, have emerged in the past five years. In this review article, we will summarize the most important research findings of targeting CRLs for radiosensitization.